Identifying the African Wintering Grounds of Hybrid Flycatchers Using a Multi–Isotope (δ (2)H, δ (13)C, δ (15)N) Assignment Approach - Veen, Thor (Public Library of Science, 2014)
Migratory routes and wintering grounds can have important fitness consequences, which can lead to divergent selection on populations or taxa differing in their migratory itinerary. Collared (Ficedula albicollis) and pied (F. hypoleuca) flycatchers breeding in Europe and wintering in different sub-Saharan regions have distinct migratory routes on the eastern and western sides of the Sahara desert, respectively. In an earlier paper, we showed that hybrids of the two species did not incur reduced winter survival, which would be expected if their migration strategy had been a mix of the parent species' strategies potentially resulting in an intermediate route crossing the Sahara desert to different wintering grounds. Previously, we compared isotope ratios and found no significant difference in stable-nitrogen isotope ratios (δ (15)N) in winter-grown feathers between the parental species and hybrids, but stable-carbon isotope ratios (δ (13)C) in hybrids significantly clustered only with those of pied flycatchers. We followed up on these findings and additionally analyzed the same feathers for stable-hydrogen isotope ratios (δ (2)H) and conducted spatially explicit multi-isotope assignment analyses. The assignment results overlapped with presumed wintering ranges of the two species, highlighting the efficacy of the method. In contrast to earlier findings, hybrids clustered with both parental species, though most strongly with pied flycatcher.